The last God-King the lives & times of Cambodia's Sihanouk - Gerrand, James ([s.l]: James Gerrand Production [production company] ; Shah Alam : Serv-U [distributor])
For 50 years, King Norodom Sihanouk Varman has been the pivot to Cambodia's destiny, juggling the fate of his people. Now in remission from cancer, King Sihanouk looks back over the highs and lows of Cambodia's struggle for survival-before, during and after'the killing field'. Accused of collaborating with Pol Pot, yet hailed as the peacemaker who ended years of carnage. How does he face his critics? How does he answer history? Here at last are the insights that make sense of Cambodia. This definitive profile draws on unique archival material as it unravels the complexities of one of the most bewildering catastropes of our century.
Excutive producer, David White; editor, Tim Litchfield
Narrator: Stuart Littlemore
Keywords: Noradom Sihanouk, -- Prince, -- 1922-; Cambodia -- Kings and rulers -- Biography